The bling dynasty : why the reign of Chinese luxury shoppers has only just begun - Rambourg, Erwan (John Wiley & Sons, 2014)
"The media has negatively focused on the Chinese political administration clamping down on gifting. Observers have come to doubt the strength of Chinese consumption as the key driver for luxury. 'The Bling Dynasty' illustrates how doubts about Chinese consumption are ill-founded and Chinese luxury demand is on the cusp of becoming dominant. This book contains the research and expert views companies need to understand and address the new challenges posed by this dominance. Each chapter brings a different perspective, covering complex aspects of luxury consumption, with illustrations and real-world examples that support the research. Readers will gain insights through interviews with brand executives, retailers, experts, and consumers. As an economic heavyweight, China is fast realizing its role in the luxury market. Chinese consumers should be accounting for more than a third of the global luxury market today, and half, if not more, in ten year's time. 'The Bling Dynasty' runs counter to the conventional wisdom that expanding sectors become more global. Luxury is actually becoming over-dependent on Chinese sales. Readers will: understand how Western brands developed in Asia and the challenges they are met with, notably ubiquity; learn why Chinese are purchasing luxury items abroad and what it means for the future of the sector; gain insights on why there are no Chinese luxury brands challenging Western models; realize that Chinese consumers are becoming similar to their American peers and that luxury competition goes way beyond pre-conceptions. China's big spenders are increasingly mobile and this is affecting key markets. 'The Bling Dynasty' provides new research and a comprehensive look at the booming business of luxury and the Chinese wallet"--Provided by publisher